PENGARUH PENGALAMAN USAHA, PERILAKU KEWIRAUSAHAAN DAN KARAKTERISTIK KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA TENUN ULOS DI KABUPATEN TOBA - ELISHA SUNIJATI; FRANCISCA FORTUNA PUTRI (LP2MTBM MAKARIOZ, 2021)
TobaRegency is the most known is the distribution of spices, vegetables to fruits. However, currently in TobaRegency, there are people who open ulos woven fabric businesses, where during the period 2018-2021 there was a decrease in the number of Ulos woven fabric business entrepreneurs in Toba Regency. This decline is due to the lack of experience in doing business from some of these Ulos woven cloth entrepreneurs, where some of these entrepreneurs do not have a strong understanding of obstacles and challenges, as well as the weaknesses and strengths of the business they are engaged in, where the business they run is still traditional and still uses the ancient buying and selling system, so that with the change in the business system, it is not ready and because many entrepreneurs are inexperienced, the behavior and attitude shown in dealing with problems are still not appropriate, so the characteristics of the business have not been able to make consumers interested in the Ulos cloth business, so that the demand for Ulos cloth is only limited when consumers organize traditional events, even though this Ulos woven cloth can be marketed in conjunction with the introduction of Tourism in TobaRegency, so it can be said that the success rate of the Ulos woven cloth business by some entrepreneurs in Toba Regency is only 20% of which the rest are trying to face challenges and want to survive to find income for the needs of life. This study aims to find out how the influence of the business experience of Ulos woven cloth entrepreneurs in Toba Regency, the entrepreneurial behavior of Ulos woven fabric entrepreneurs in Toba Regency and the entrepreneurial characteristics of Ulos woven fabric entrepreneurs in Toba Regency have a positive and significant effect on the success of the Ulos woven fabric business in Toba regency. The total population in this study is 167 Ulos woven cloth business entrepreneurs in Toba Regency, where the sampling technique uses saturated techniques with a total sample of 167 Ulos woven cloth entrepreneurs in Toba Regency. The results of the study can be concluded that simultaneously and partially the variables of business experience of Ulos woven cloth entrepreneurs in Toba Regency, the entrepreneurial behavior of Ulos woven cloth entrepreneurs in Toba Regency and the entrepreneurial characteristics of Ulos woven fabric entrepreneurs in Toba Regency have a positive and significant influence on the variable success of the Ulos woven fabric business in Toba Regency